Negara Kesejahteraan dan Maqasid Syariah: Analisis Pemikiran Jamaluddin Athiyyah - Syamsuri Syamsuri; Dadang Irsyamuddin (Falah: Jurnal Ekonomi Syariah, 2019)
The discourse about the Welfare State is interesting. This article aims to conduct in-depth analysis related to the concept of the welfare state and its relation to maqasid sharia according to Jamaluddin Athiyyah. The method used in this study is qualitative with a literature approach, namely conducting a study of the literature surrounding the welfare state and the Maqasid sharia. The conclusion of this study is that Athiyyah provides an overview of the division of tasks of the government in ensuring the welfare of its people into four dimensions, namely: individuals, families, society and humanity. Furthermore it was stated that the three basic principles of maqasid sharia to create prosperity would not be fulfilled but rather with the active role of the State.